Comparison of Preservatives for the Prevention of Microbial Spoilage of Apple Pomace During Storage - Ashley Harratt; Wenyuan Wu; Peyton Strube; Joseph Ceravolo; David Beattie; Tara Pukala; Marta Krasowska; Anton Blencowe (Foods)
Apple pomace, a by-product from the production of concentrated juice, is a major contributor to global food waste. Despite its beneficial nutritional profile, apple pomace is predominantly disposed of in landfills. Rapid fermentation and spoilage caused by microorganisms are compounding factors in this demise, despite significant research into upcycling strategies. Thus, there is an unmet need for economical approaches that allow for the preservation of pomace during storage and transportation to centralized processing facilities from regional hubs. To address this challenge, we investigated the potential of different preservatives for preventing microbial growth and the spoilage of apple pomace, including antimicrobials (natamycin and iodine), polysaccharides (chitosan and fucoidan), and acetic acid. Spread plates for total microbial and fungal counts were employed to assess the effectiveness of the treatments. High concentrations (10,000 ppm) of chitosan were effective at reducing the microbial load and inhibiting growth, and in combination with antimicrobials, eliminated all microbes below detectable levels. Nevertheless, acetic acid at an equivalent concentration to commercial vinegar displayed the highest economic potential. Apple pomace submerged in 0.8 M acetic acid (3 kg pomace per liter) resulted in a five-log reduction in the microbial colony-forming units (CFUs) out to 14 days and prevented fermentation and ethanol production. These results provide a foundation for the short-term storage and preservation of apple pomace that could contribute to its upcycling.